Al-Qur’an dan Arkeologi: Studi Interdisipliner dalam Memahami Sejarah Peradaban Manusia - Muhammad Abbas (ANWARUL, 2026)
Although the relationship between the Qur’an and the history of human civilization has received attention in various Islamic and historical studies, research that specifically integrates Qur’anic perspectives and archaeological findings within a single interdisciplinary framework remains limited. This study aimed to analyze the contribution of an interdisciplinary approach between the Qur’an and archaeology to understanding the history of human civilization and its implications for the historical interpretation of Qur’anic verses. The study employed a qualitative approach with a library research design, using primary sources in the form of Qur’anic verses related to narratives of past civilizations and secondary sources consisting of archaeological data documented in scholarly literature. Data were collected through document review and analyzed using thematic-comparative analysis. The findings indicate that archaeological discoveries, such as ancient settlement sites, cultural artifacts, and evidence of civilizational collapse, correspond with Qur’anic narratives about earlier peoples, including the ‘Ād, Thamūd, and Fir‘aun. These findings strengthen the understanding that the Qur’an functions not only as a theological text but also has historical and civilizational dimensions that are relevant to modern scholarly inquiry. The study concludes that integrating Qur’anic and archaeological approaches is important for developing a more comprehensive understanding of the history of human civilization. The implications include a theoretical contribution to the development of thematic-historical tafsīr studies and practical implications for advancing Islamic education grounded in knowledge integration, while also opening opportunities for further research on dialogue between revelation and science in the context of history and civilization.